Moving toward a spiritual pedagogy in L2 education: Research, practice, and applications - Song, Dongmei (Frontiers in Psychology, 2022)
Spiritual pedagogy (SP) as a new educational theory aims to apply cultural and spiritual values in classroom practices. It has been the focus of research in different fields such as counselling, management, and science in the past decades. However, its application in second/foreign language research and practice has been widely overlooked by L2 researchers, to date. To fill this gap, the present study made an effort to provide a theoretical analysis of the conceptualizations, scientific background, benefits, and practical techniques to implement SP in the context of L2 education. In so doing, this paper suggests a number of practices through which SP can be integrated into L2 education among which positive psychology (PP) were more highlighted. Additionally, some practical implications were provided for EFL teachers, teacher trainers, students, curriculum designers, and researchers to enhance their knowledge of spirituality and education. In the end, different suggestions for future research were presented to move this research domain forward.